107k views
1 vote
How to solve y=-3x+4 y+3x=-4

User Mikej
by
4.9k points

1 Answer

0 votes

using simultaneous method

from equation 1


\begin{gathered} y=-3x+4 \\ \end{gathered}

put this in equation 2


\begin{gathered} y+3x=-4 \\ \text{but y = -3x + 4} \\ (-3x+4)+3x=-4 \\ -3x+4+3x=-4 \\ \text{collect like terms} \\ -3x+3x=-4-4 \\ 0=-8 \\ or\text{ x = 0} \end{gathered}

put x = 0 in either equation 1 or 2


\begin{gathered} y=-3x+4 \\ y=-3(0)+4 \\ y=4 \end{gathered}

x = 0, y = 4

using graph

How to solve y=-3x+4 y+3x=-4-example-1
User Masto
by
4.4k points